Neoproterozoic chemostratigraphy and correlation of the Port Askaig glaciation, Dalradian Supergroup of Scotland - Brasier, M; Shields, G (2000)
The δ13C of preglacial carbonates beneath the glaciogenic Port Askaig Formation falls from +5‰ to negative values, while least-altered 87Sr/86Sr values are close to 0.7067. Postglacial 'cap carbonates' of the Bonahaven Formation begin with negative δ13C(carb) values, jumping sharply to +11.7‰ near the top, which we correlate with excursions above the Elbobreen-Wilsonbreen glaciations of Svalbard and putative Sturtian (not Varanger) glaciations elsewhere, dated at c. 720 Ma. Much of the succeeding Terminal Neoproterozoic is missing in NE Svalbard and East Greenland, raising doubts about their use for global Sr and C isotope curves in the Neoproterozoic.